2022
DOI: 10.1079/hai.2022.0015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human-Animal Interactions on Affect and Cognition

Abstract: Human-animal interaction has clear positive effects on people’s affect and stress. But less is known about how animal interactions influence cognition. We draw parallels between animal interactions and exposure to natural environments, a research area that shows clear improvements in cognitive performance. The aim of this study is to investigate whether interacting with animals similarly enhances cognitive performance, specifically executive functioning. To test this, we conducted two experiments in which we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…In a neuroimaging study by Nagasawa et al [ 62 ], participants demonstrated greater prefrontal cortex activation when interacting with a cat, with the authors concluding that this may transfer to overall EF ability. In comparison, Thayer and Stevens [ 64 ] found no significant changes in EFs when interacting with a dog across two independent experiments, as measured by performance on WM tasks. Similarly, results from Gee et al’s [ 60 ] counterbalanced study were mixed, with participants improving in EF task performance when either the human collaborator or the dog were simply sitting next to the participant.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…In a neuroimaging study by Nagasawa et al [ 62 ], participants demonstrated greater prefrontal cortex activation when interacting with a cat, with the authors concluding that this may transfer to overall EF ability. In comparison, Thayer and Stevens [ 64 ] found no significant changes in EFs when interacting with a dog across two independent experiments, as measured by performance on WM tasks. Similarly, results from Gee et al’s [ 60 ] counterbalanced study were mixed, with participants improving in EF task performance when either the human collaborator or the dog were simply sitting next to the participant.…”
Section: Resultsmentioning
confidence: 98%
“…Two of the studies did not provide enough detailed information to determine the time spent in the overall experiment (e.g., greeting researchers, receiving instructions, testing with animal present, finishing experiment) versus actual time spent directly interacting with the animal. Of the four studies that provided information about the total time spent with the animal [ 59 , 62 , 63 , 64 ], interactions ranged between 3 min and 15 min in length ( M time = 6.25, SD = 5.85).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations